Puyang Dalam Kepercayaan Masyarakat Desa Ujanmas Lama Kecamatan Ujanmas Kabupaten Muara Enim - Abdi Harwedi; Endang Rochmiatun; Otoman Otoman (Program Studi Sejarah Peradaban Islam UIN Raden Fatah Palembang, 2022)
This study attempts to describe the beliefs of the people of Ujanmas Lama Village towards the puyang and the traditions carried out by the community in respecting the puyang. The method used is the ethnographic method by conducting direct observations, interviews, and documentation. The results showed that the people of Ujanmas Lama Village understood puyang as ancestors or figures who had established a village. This makes the people of Ujanmas Lama Village very respectful of their puyang, so that people have confidence in the magical or supernatural powers of the puyang. People believe that anything that becomes a legacy is something that must be considered sacred and has spiritual power. From this community belief, people have great respect for puyang. The respect of the puyang in some of what is done by the pilgrimage community to the puyang tomb, such as to the objects of the puyang heritage, and the implementation of customary law that has existed since the kepuyangan era.